THE THEME OF THE DEPORTATION OF THE CHECHEN PEOPLE IN THE GRAPHIC CYCLE CROSSROADS OF MEMORY (1944-2019) BY RUSTAM YAKHIKHANOV - Zarema R. Khamzatova (Russian Studies in Culture and Society, 2023)
This study is the first to present an analysis of previously unexplored works that serve as an artistic response to the tragic events in the history of the Chechen people in 1944. Using the works of the graphic cycle by artist R. Yakhihhanov as an example, the study reveals the peculiarities of interpreting ideas and plots to unfold the theme of deportation. Drawing on the life experiences of senior family members and relatives who suffered political repression, the artist conveys personal tragedies and losses to the viewer.